Magnitude and associated factors of intraoperative cardiac complications among geriatric patients who undergo non-cardiac surgery at public hospitals in the southern region of Ethiopia: a multi-center cross-sectional study in 2022/2023 - Abdulmelik, Amina; Tila, Mebratu; Tekilu, Takele; Debalkie, Ashebir; Habtu, Elias; Sintayehu, Ashagrie; Dendir, Getahun; Gordie, Naol; Daniel, Abel; Suleiman Obsa, Mohammed (Frontiers in Medicine, 2024)
Background Intraoperative cardiac complication is common cause of morbidity and mortality in non-cardiac surgery. The risk of these complications raising with the average age increasing from 65. In a resource-limited setting, including our study area, the magnitude and associated factors of intraoperative cardiac complications have not been adequately investigated. The aim of this study to assess the magnitude and associated factors of intraoperative cardiac complications among geriatric patients undergoing non-cardiac surgery. Methods: Institutional-based multi-center cross-sectional study was conducted on 304 geriatric patients at governmental hospitals in the southern region, Ethiopia, from March 20, 2022–August 25, 2022. Data collected by chart review and patient interviews. Epi Data version 4.6 and SPSS version 25 used for analysis. The variables that had association (p<0.25) were considered for multivariable logistic regression. A p-value of <0.05 was used as significant. Result: The overall prevalence of intraoperative cardiac complications was 24.3%. Preoperative ST-segment elevation (AOR=2.43, CI =2.06-3.67), history of hypertension (AOR=3.42, CI = 2.02-6.08), intraoperative hypoxia (AOR=3.5, CI= 2.07- 6.23), intraoperative hypotension (AOR=6.2 9, CI =3.51-10.94), patients age > 85 (AOR = 6.01, CI = 5.12-12.21) and anesthesia time > 3 hours (AOR =2.27, CI=2.0.2-18.25) were factors significantly associate to intraoperative cardiac complication. Conclusion: The intraoperative cardiac complications are common among geriatric patients undergone noncardiac surgery. Extensive preoperative evaluation, and knowing all possible factors, suggested to reduce the occurrence of complication.